2017
DOI: 10.1111/cob.12189
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes remission rates 1‐year post‐Roux‐en‐Y gastric bypass and validation of the DiaRem score: the Ontario Bariatric Network experience

Abstract: Roux-en-Y gastric bypass (RYGB) is associated with the remission of type 2 diabetes mellitus (DM). There are a number of scoring systems available that help predict type 2 diabetes remission rates after bariatric surgery; however, relatively few have been validated externally. The DiaRem score, comprised of four preoperative variables (age, haemoglobin A1c [HbA1c], sulfonylurea and insulin-sensitizing agent use and insulin use), allows for the identification of patients who are most likely to have DM remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…The calculation of DiaRem score stratifies individuals within 5 categories of ascending score, providing a probability of remission achievement [77]. The DiaRem score is a practical clinical tool and has undergone external validation [80,81,82]. Although its application cannot be directly extrapolated to types of surgery other than RYGB, there is limited data supporting its applicability to VSG and possibly also to AGB [83,84].…”
Section: Factors That Predict T2dm Remission After Bariatric Surgerymentioning
confidence: 99%
“…The calculation of DiaRem score stratifies individuals within 5 categories of ascending score, providing a probability of remission achievement [77]. The DiaRem score is a practical clinical tool and has undergone external validation [80,81,82]. Although its application cannot be directly extrapolated to types of surgery other than RYGB, there is limited data supporting its applicability to VSG and possibly also to AGB [83,84].…”
Section: Factors That Predict T2dm Remission After Bariatric Surgerymentioning
confidence: 99%
“…The findings showed that at one-year follow-up after RYGB, 37% of individuals had remitted, and the clinical factors within the DiaRem score were associated with this remission. A helpful DiaRem cutoff score of <5 (71.8% sensitivity, 71.3% specificity) was established by this study, and they concluded that this scoring system had a moderate predictive value at best [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…Obesity is one of the leading global causes of preventable deaths and has rapidly become a health issue of epidemic proportions, impacting people of all ages, from children and adolescents to adults [ 1 , 2 , 3 ]. The connection between obesity and diabetes has been well researched and documented [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using retrospective data, preoperative scoring models (DiaRem, Ad-DiaRem, DiaBetter) have been developed and validated to accurately predict T2D remission up to 5 years after gastric bypass surgery [4][5][6][7][8][9][10]. However, preoperative prediction of T2D relapse after initial remission seems more challenging and it has been suggested that in addition to preoperative Electronic supplementary material The online version of this article (https://doi.org/10.1007/s11695-020-04763-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%